Keratinocyte Growth Factor 2 Ameliorates UVB-Induced Skin Damage via Activating the AhR/Nrf2 Signaling Pathway - Gao, Shuang; Guo, Keke; Chen, Yu; Zhao, Jungang; Jing, Rongrong; Wang, Lusheng; Li, Xuenan; Hu, Zhenlin; Xu, Nuo; Li, Xiaokun (Frontiers in Pharmacology, 2021)
Objective: Exposure to ultraviolet B (UVB) can cause skin damage through oxidative stress, DNA damage, and apoptosis. Keratinocyte growth factor (KGF) has been shown to reduce the content of intracellular reactive oxygen species (ROS) following UVB exposure, a role that is crucial for the efficient photoprotection of skin. The present study evaluated the photoprotective effect of KGF-2 on UVB-induced skin damage and explored its potential molecular mechanism. Methods: To evaluate the effect of KGF-2 on UVB-induced damage ex vivo, a human epidermal full-thickness skin equivalent was pretreated without or with KGF-2 and then exposed to UVB and the levels of histopathological changes, DNA damage, inflammation and apoptosis were then evaluated. The ability of KGF-2 to protect the cells against UVB-inflicted damage and its effect on ROS production, apoptosis and mitochondrial dysfunction were determined in HaCaT cells. Results: Pretreatment of the epidermis with KGF-2 ameliorated the extent of photodamage. At the cellular level, KGF-2 could attenuate ROS production, apoptosis, DNA damage and mitochondrial dysfunction caused by UVB exposure. KGF-2 could also activate the aryl hydrocarbon receptor (AhR) to trigger the Nrf2 signaling pathway. Conclusion: Taken together, our findings suggested that KGF-2 could ameliorate UVB-induced skin damage through inhibiting apoptosis, reducing oxidative stress, and preventing DNA damage and mitochondrial dysfunction via regulating AhR/Nrf2 signaling pathway.